Comparative analysis of Microsoft’s ,,low-code” programming technology - Grzegorz Łopata; Konrad Gromaszek (Journal of Computer Sciences Institute)
According to various investigations, ‘low code’ platforms will form a large part of software development’s market in the future. In that research paper was executed a comparison of Power Fx language functions: Patch, UpdateIf, SubmitForm and graphical interfaces, which allow making applications in Power Apps, were subjected to analysis. Research paper has shown that the average time of data recording into Dataverse using Patch function was slightly shorter than using SubmitForm. Moreover, it was found, that the average time required by the test group for creation Model – Driven app was 40% less than the average time for creation Canvas app and was demonstrated that a graphical interface, which enables making Power Apps Canvas is more efficient than Model – Driven graphical interface.